Communication Skills for Nurses : a Practical Guide on How to Achieve Successful Consultations - Edwards, Marilyn (Quay Books Division, MA Healthcare, Ltd., 2010)
Over a third of all consultations in general practice are now conducted by nurses. The consultation is the key element of primary care, with patients being more satisfied with the care given by clinicians who have good communication skills. Poor communication or dissatisfaction with a consultation is reported to be one reason why patients decide not to attend or do not take a prescribed treatment. Patients need to be satisfied with the consultation, understand their condition and understand ...